Travelling objects : changing values : the role of Northern Alpine lake-dwelling communities in exchange and communication networks during the late Bronze Age - Jennings, Benjamin, (Archaeopress archaeology., 2014)
Since their initial discovery in the nineteenth century, the enigmatic prehistoric lake-dwellings of the Circum-Alpine region have captured the imagination of the public and archaeologists alike. Over 150 years of research have identified hundreds of lacustrine settlements spanning from the Neolithic to the Late Bronze Age, when apparently, they ceased to be built. Studies of Bronze Age material across Europe have often superficially identified bronze objects as being of 'Alpine lake-dwelling origin' or 'lake-dwelling style'. Through a combination of material culture studies, multiple correspondence analysis, and the principle of object biographies, the role of the Late Bronze Age lake-dwelling communities in Central European exchange networks is addressed.